Perancangan Penukar Panas Aliran Silang untuk Produksi Jamur Merang - Willy Achmad Wildan F; Oleh Oleh; Iman Dirja (Peneliti.net, 2022)
Preheater is one form of heat exchanger which serves to heat the working fluid to be fed to the next heating arrangement. Generally the source of thermal energy used is exhaust gas that still has a high temperature obtained from the previous heating system. The amount of heat flow rate given by the hot gas to the water in the pipe is able to provide hot water supply. Construction planning preheater made such use LMTD approach and effectiveness as well as the integrated CFD simulation on Anys15.4, so it can be seen that the performance of the tool. The final results of modeling provide flow and temperature distribution occurs in the heat exchanger. The capitalization use 3D steady flow by choosing K-ℇ turbulence modeling standards as well as to enable the energy equation. Data inputs are incorporated into the application is the result of measurements and calculations done before